2015
DOI: 10.14800/rd.864
|View full text |Cite
|
Sign up to set email alerts
|

RNA Networks that Regulate mRNA Expression and their Potential as Drug Targets

Abstract: Natural antisense transcripts (asRNAs) transcribed from eukaryotic genes are primarily long transcripts that do not code for proteins. Transcriptome analyses have revealed that asRNAs exhibit diverse functional roles in the regulation of gene expression. In the case of inducible genes, asRNAs epigenetically affect their expression or post-transcriptionally affect stability and translatability of their mRNAs. Many low-copy-number asRNAs regulate the expression levels of mRNAs through cis-controlling elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We hypothesized that PTEN mRNA and other miR-17-92 targets, including p21 mRNA, may act as competing endogenous RNAs (ceRNAs), which are RNAs sharing miRNA recognition elements (MREs) with other RNAs (such as mRNA and long non-coding RNA), as common targets against the miRNA [ 20 ]. Depending on the miRNA affinity, variable post-transcriptional regulation of one or more genes may occur among all miRNA targets [ 20 , 21 ]. To examine the above hypothesis, we constructed lentiviral vectors expressing a DsRed coding region fused with each segment of the six consecutive regions (a–f) or the full-length PTEN 3′ UTR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that PTEN mRNA and other miR-17-92 targets, including p21 mRNA, may act as competing endogenous RNAs (ceRNAs), which are RNAs sharing miRNA recognition elements (MREs) with other RNAs (such as mRNA and long non-coding RNA), as common targets against the miRNA [ 20 ]. Depending on the miRNA affinity, variable post-transcriptional regulation of one or more genes may occur among all miRNA targets [ 20 , 21 ]. To examine the above hypothesis, we constructed lentiviral vectors expressing a DsRed coding region fused with each segment of the six consecutive regions (a–f) or the full-length PTEN 3′ UTR.…”
Section: Resultsmentioning
confidence: 99%
“…In general, miRNAs inhibited the stability and translation of mRNAs by forming an RNA-induced silencing complex that bound to a partially complementary sequence called MRE in their target genes. ceRNAs are a variety of RNA, including long non-coding RNA and mRNA with the same MRE, and they competitively share the same miRNA pool [ 20 , 21 ]. During iPSC reprogramming, we demonstrated that the miR-17-92-dependent downregulation of PTEN was influenced by p21 transcript levels, suggesting that miR-17-92 preferentially repressed p21 rather than PTEN in the early-to-mid phase when p21 mRNA expression was upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Upon inhibition of the miR-200 family in a gastric carcinoma cell line, the up-regulated repressors suppress E-cadherin expression, resulting in EMT (95). Indeed, transfection of BARF0, EBNA1, and LMP2A expression plasmids downregulated the transcription of pri-miR-200 RNAs, whereas EBER1 post-transcriptionally inhibited miR-200 action (95), possibly acting as a ceRNA (competing endogenous RNA) to sequester the miR-200 family (96,97).…”
Section: Hpv Mirnas and Oncogenesismentioning
confidence: 99%